A transgenic mouse line for collecting ribosome-bound mRNA using the tetracycline transactivator system - Drane, Laurel; Ainsley, Joshua A.; Mayford, Mark R.; Reijmers, Leon G. (Frontiers in Molecular Neuroscience, 2014)
Acquiring the gene expression profiles of specific neuronal cell-types is important for understanding their molecular identities. Genome-wide gene expression profiles of genetically defined cell-types can be acquired by collecting and sequencing mRNA that is bound to epitope-tagged ribosomes (TRAP; Translating Ribosome Affinity Purification). Here, we introduce a transgenic mouse model that combines the TRAP technique with the tetracycline transactivator (tTA) system by expressing EGFP-tagged ribosomal protein L10a (EGFP-L10a) under control of the tetracycline response element (tetO-TRAP). This allows both spatial control of EGFP-L10a expression through cell-type specific tTA expression, as well as temporal regulation by inhibiting transgene expression through the administration of doxycycline. We show that crossing tetO-TRAP mice with transgenic mice expressing tTA under the Camk2a promoter (Camk2a-tTA) results in offspring with cell-type specific expression of EGFP-L10a in CA1 pyramidal neurons and medium spiny neurons in the striatum. Co-immunoprecipitation confirmed that EGFP-L10a integrates into a functional ribosomal complex. In addition, collection of ribosome-bound mRNA from the hippocampus yielded the expected enrichment of genes expressed in CA1 pyramidal neurons, as well as a depletion of genes expressed in other hippocampal cell-types. Finally, we show that crossing tetO-TRAP mice with transgenic Fos-tTA mice enables the expression of EGFP-L10a in CA1 pyramidal neurons that are activated during a fear conditioning trial. The tetO-TRAP mouse can be combined with other tTA mouse lines to enable gene expression profiling of a variety of different cell-types.